The Roman Inquisition Revisited The Maltese Tribunal in the Eighteenth Century - Ciappara, Frans 1946- (2017)
This article deals with the Roman inquisition in Malta during the eighteenth century when much of its severity had declined. It presents evidence from primary sources in Malta's inquisitorial archives to document unique aspects of the Maltese tribunal and, in the process, demolishes various myths about this institution. It proves that most of the charges resulted from self-confessions and that the accused would be arrested only after a prolonged investigation. Though he was not supplied with the names of his accusers these did crop up during interrogation. They were also to be found in the transcript that a defendant was given to prepare his defense with and he was even able to confront his accusers face to face. The defendant was permitted to have a lawyer to assist him and could bring his own witnesses. Judicial torture was rarely used and sentences were decided with much circumspection so that the innocent would not be punished. It is morally incorrect to condemn liberty of conscience but it must be said that the Roman inquisition followed the rule of law.